The effect of optimism on the facial expression of pain: Implications for pain communication. (16th March 2021) - Basten‐Günther, Johanna; Kunz, Miriam; Peters, Madelon; Lautenbacher, Stefan
Abstract: Background: There is a broad range of evidence on optimism dampening the pain experience, as assessed by subjective self‐report. Facial expression of pain conveys supplementary information about the pain experience, is an integral part of pain communication and assists psychosocial pain coping. Nevertheless, the effect of induced optimism on facial activity during pain has to our knowledge not been examined. Methods: In our experiment, 40 healthy participants underwent two blocks of thermal stimulation containing phasic non‐painful and painful stimuli. Between the two blocks, the Best Possible Self imagery and writing task was performed to induce situational optimism, while a control group wrote about their typical day. Facial activity and self‐report ratings of intensity and unpleasantness were recorded. Facial activity was analysed using the Facial Action Coding System. Results: The optimism manipulation was successful in increasing state optimism. It did not affect self‐report ratings, but resulted in a stronger facial expression of pain, caused especially by increases in Action Units 4 (furrowed brows) and 6_7 (narrowed eyes). Conclusions: All Action Units, which were affected by the optimism induction, are known to be prevalent during pain stimulation. The increase in facial expression might reflect reduced inhibition of pain communication in temporarily optimistic participants. Optimism might lead to expecting positive and helpful reactions from others and, by that, to great readiness to elicit these reactions by non‐verbal social behaviour. Significance: This study is the first to indicate that state optimism increases the facial expression of pain as a social signal for help and empathy without concomitant changes in the subjective pain experience.